Effect of mechanical activation on kaolin-based geopolymers - Cheng, Yong Heah; Kamarudin, Hussin, Brig. Gen. Dato' Prof. Dr.; Mohd Mustafa Al-Bakri, Abdullah; Mohammed, Hussain; Luqman, Musa; Khairul Nizar, Ismail, Assoc. Prof. Dr.; Che Mohd Ruzaidi, Ghazali; Liew, Y. M. (Trans Tech Publications, 2013)
Link to publisher's homepage at http://www.ttp.net/